Retracted: Anomaly detection with ensemble empirical mode decomposition and approximate entropy for quick user datagram protocol internet connection‐based distributed Blockchain systems - Yuanlong Cao; Keyang Gu; Junyi Wu; Xiang Zou; Lei Tao; Xin Huang; Changgen Jiang (IET Software)
Abstract Retraction: [Yuanlong Cao, Keyang Gu, Junyi Wu, Xiang Zou, Lei Tao, Xin Huang, Changgen Jiang, Anomaly detection with ensemble empirical mode decomposition and approximate entropy for quick user datagram protocol internet connection‐based distributed Blockchain systems, IET Software 2023 (https://doi.org/10.1049/sfw2.12096)]. The above article from IET Software, published online on 20 January 2023 in Wiley Online Library (wileyonlinelibrary.com), has been retracted by agreement between the Editor‐in‐Chief, Hana Chockler, the Institution of Engineering and Technology (the IET) and John Wiley and Sons Ltd. This article was published as part of a Guest Edited special issue. Following an investigation, the IET and the journal have determined that the article was not reviewed in line with the journal’s peer review standards and there is evidence that the peer review process of the special issue underwent systematic manipulation. Accordingly, we cannot vouch for the integrity or reliability of the content. As such we have taken the decision to retract the article. The authors have been informed of the decision to retract.